Comparison between methods of evaluation of soybean mechanized harvesting losses - Muncio Compagnon, Ariel (2012)
The soybean is of great importance in the Brazilian agricultural scenario and both productivity and the area cultivated to each crop are increasing, demanding more speed and quality at harvest. However, losses are recorded in the mechanical harvesting of soybeans, a fundamental stage in the production process of field crops. Looking to quantify these losses was used in this study display a loss, and results were compared with the losses collected manually. Data were collected at Fazenda São Luiz, in the city of Santa Juliana - MG, with a harvester dual-rotor axial, with a platform of 9.14 m. We assessed 40 points in the day and night periods, and the variables: water content of grains, travel speed, plant height, height of first pod, grain yield, losses due to disability at the time of cutting, trail system, cleaning system and total grain losses and losses in the separation of clean grain. The soybean harvest at night had higher levels of coincidence between the obtained sensor separation and the losses measured in the field, while during the day there was a better match for the sensor track. Losses of grain deficiency in cutting height contribute largely to the loss of soybeans at harvest during the day, reducing the correlation between the losses estimated in the field and the losses obtained from the sensors.